Analysis of Job Embeddedness as Mediation in the Relationship between Work Life Balance on Turnover Intention - Muhammad Faisal Ramadanu; Guntur Syahputra Saragih; Iwan Kresna Setiadi; Sumilir Sumilir; Yudi Nur Supriadi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
This research has the primary aim of delving deeper into the relationship between work-life balance and turnover intention while considering job embeddedness as an intermediary factor. A total of 180 employees participated in this study, which used a quantitative research approach. Data analysis was conducted using the Structural Equation Model (SEM) with the application of the Partial Least Square (PLS) methodology. The research findings highlight that work-life balance significantly influences the likelihood of turnover intention among employees. However, it's important to note that while work-life balance does affect job embeddedness, this effect doesn't directly translate into affecting turnover intention when the mediation of job embeddedness is considered. This research holds substantial significance for organizations as it offers a deeper understanding of strategies to minimize turnover rates, ultimately contributing to the establishment of a robust and sustainable business framework in the long term. This emphasizes the critical role of effective human resource management in achieving these objectives. Keywords : Work Life Balance, Job Embeddedness, Organizational Commitment, Turnover Intention.